Pembuatan Nugget Ikan Tongkol (Euthynnus Affinis) Dengan Penambahan Tepung Kelor (Moringa Oleifera) Sebagai Upaya Peningkatan Nilai Gizi - Untari, Desy Sasri; Rahmawati, Annisa; Wibowo, Tri Adi (JURNAL PENGOLAHAN PERIKANAN TROPIS, 2024)
Nuggets are generally made from chicken meat. However, along with the times, people are able to process nuggets with various processed variants such as beef to fish. The purpose of this study is to determine the level of nutritional value contained in Cod Fish Nuggets given with the addition of moringa leaf flour and to determine the increase in nutritional value with the addition of moringa leaf flour to the product. This study is quantitative data that uses a research method based on positivistic (concrete data), This study uses proximate testing which includes water (moisture), ash (ash), crude protein, crude fat (ether extract), and nitrogen free extract to compare between cod fish nuggets without the addition of moringa leaves and those given the addition of moringa leaves. Based on the results, the use of moringa leaves in nugget products provides nutritional differences based on the results of the proximate test. The nutritional content contained in the Cod Fish Nuggets given with the addition of moringa leaf flour obtained test results that showed an increase in protein content of 1.6854% to 4.3665% and a decrease in fat content from 0.8418% to 0.4191%, an increase in crude fiber content of 1.2084% to 1.6721%, ash content of 0.8418% to 1.3115%, water content of 39.9439% to 47.0910% and and carbohydrates decreased from 50.7263 to 43.6515 in nugget products.